The GABAA receptor RDL modulates the auditory sensitivity of malaria mosquitoes - David A. Ellis; Alexandros C. Alampounti; Anya Suppermpool; Marcos Georgiades; Elizabeth Freeman; Judit Bagi; Scott Tytheridge; Daniela Terrazas-Duque; Joerg T. Albert; Marta Andrés (iScience)
Summary: Malaria mosquitoes acoustically detect mating partners through their flight tones in noisy swarms. Here, we study the auditory role of GABA, one of the main efferent signaling molecules in the mosquito ear, and its interactions with octopamine. We show that GABA signals through the GABAA receptor resistance to Dieldrin (RDL), an insecticide target. Using picrotoxin to antagonize RDL receptors, we report multilevel auditory effects of GABA. Mechanically, picrotoxin promotes changes in the ear’s anatomy and mechanical state. Because these effects are abolished in octopamine receptor AgOctβ2 knockouts, they appear to be octopamine dependent. Electrically, picrotoxin increases the spontaneous firing of the antennal nerve and enhances mechanically evoked responses. These effects are partially present in AgOctβ2 mutants, suggesting that RDL modulates electrical responses via octopamine-independent pathways. Together, our experiments show an important role of RDL in controlling malaria mosquito auditory sensitivity and implicate RDL in mating of natural malaria mosquito populations.